2022
DOI: 10.1039/d1cy02144c
|View full text |Cite
|
Sign up to set email alerts
|

Titania-supported molybdenum oxide combined with Au nanoparticles as a hydrogen-driven deoxydehydration catalyst of diol compounds

Abstract: A heterogenous catalyst for deoxydehydration (DODH) reaction was developed using less expensive Mo than Re as the active center. Combination of Mo with anatase-rich TiO2 and Au as the support...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 74 publications
3
48
0
Order By: Relevance
“…144,145 ReO x -Ag/CeO 2 catalyzed the DODH of 1,4-AHERY with H 2 to produce 2,5-dihydrofuran in high yield (∼88%) with 5% yield of 2,3-dihydrofuran. 147 It was also reported recently that MoO x -Au/ TiO 2 and MoO x -Pd/TiO 2 emerged as good catalysts for the DODH of 1,4-AHERY with H 2 to form 2,5-dihydrofuran (77% yield) 148 and tetrahydrofuran, 148,244 respectively. Although high selectivity was reported, the activity of the MoO x -M/TiO 2 -catalyzed system was significantly lower than that of the ReO x -M/ CeO 2 -catalyzed systems (higher reaction temperature or lower initial reaction rate), because of the intrinsic lower activity of Mo species in DODH than that of Re.…”
Section: Deoxydehydration (Dodh) and Dodh + Hydrogenation Of Erythritolmentioning
confidence: 72%
See 1 more Smart Citation
“…144,145 ReO x -Ag/CeO 2 catalyzed the DODH of 1,4-AHERY with H 2 to produce 2,5-dihydrofuran in high yield (∼88%) with 5% yield of 2,3-dihydrofuran. 147 It was also reported recently that MoO x -Au/ TiO 2 and MoO x -Pd/TiO 2 emerged as good catalysts for the DODH of 1,4-AHERY with H 2 to form 2,5-dihydrofuran (77% yield) 148 and tetrahydrofuran, 148,244 respectively. Although high selectivity was reported, the activity of the MoO x -M/TiO 2 -catalyzed system was significantly lower than that of the ReO x -M/ CeO 2 -catalyzed systems (higher reaction temperature or lower initial reaction rate), because of the intrinsic lower activity of Mo species in DODH than that of Re.…”
Section: Deoxydehydration (Dodh) and Dodh + Hydrogenation Of Erythritolmentioning
confidence: 72%
“…The general scheme of DODH with H 2 reductant is shown in Fig. 12, and the reported catalysts for this type of reaction are ReO x -Au/CeO 2 , [144][145][146] ReO x -Ag/ CeO 2 , 147 MoO x -Au/TiO 2 , 148 ReO x /C, 149 and CH 3 ReO 3 . 150 Most of these catalysts are bimetallic.…”
Section: Double-hydrodeoxygenation Of Alkyl Glycosides With Cis-vicin...mentioning
confidence: 99%
“…This finding, along with the catalytic results over individual Pt/r-TiO 2 and WO x /r-TiO 2 , unambiguously confirms that when r-TiO 2 is used as the support of Pt, hydrogen spillover from the Pt NPs to the WO x species is highly efficient and does not require direct contact, and the Pt/r-TiO 2 domain plays the role of providing spillover hydrogen atoms, and the WO x domain plays the roles of adsorbing glycerol and the active site for 1,3-PDO formation. Similarly, Tomishige and co-workers reported in a recent work that in 1,4-anhydroerythritol deoxydehydration with H 2 as the reducing agent, the physically mixed MoO x /P25 + Au/P25 catalyst was highly active, while individual MoO x /P25 and Au/P25 were essentially inactive . It was also found that hydrogen spillover from Ni/r-TiO 2 to Ni/a-TiO 2 could take place when they were physically mixed .…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Tomishige and co-workers reported in a recent work that in 1,4-anhydroerythritol deoxydehydration with H 2 as the reducing agent, the physically mixed MoO x /P25 + Au/P25 catalyst was highly active, while individual MoO x /P25 and Au/ P25 were essentially inactive. 67 It was also found that hydrogen spillover from Ni/r-TiO 2 to Ni/a-TiO 2 could take place when they were physically mixed. 55 The enhanced activity of the Pt/ r-TiO 2 + WO x /r-TiO 2 catalyst with respect to the Pt−WO x /r-TiO 2 catalyst is attributed to the fact that on monometallic Pt/ r-TiO 2 , the Pt NPs are not blocked by WO x , thus providing more spillover hydrogen atoms for glycerol hydrogenolysis.…”
Section: ■ Resultsmentioning
confidence: 97%
“…In fact, Mo and Re play a similar role in various catalysts for oxygen removal reactions. For instance, Tomishige et al 105 developed a heterogeneous catalyst for the DODH reaction. The combination of Mo with anatase-rich TiO 2 and Au as the support and promoter for H 2 activation, respectively, can selectively convert 1,4-AHERY to 2,5-DHF, which is a typical DODH model reaction, with H 2 as a reducing agent.…”
Section: Bio-based 14-bdo and Thf Synthesismentioning
confidence: 99%